2018
DOI: 10.5194/angeo-36-1-2018
|View full text |Cite
|
Sign up to set email alerts
|

Energy conversion through mass loading of escaping ionospheric ions for different Kp values

Abstract: Abstract. By conserving momentum during the mixing of fast solar wind flow and slow planetary ion flow in an inelastic way, mass loading converts kinetic energy to other forms -e.g. first to electrical energy through charge separation and then to thermal energy (randomness) through gyromotion of the newly born cold ions for the comet and Mars cases. Here, we consider the Earth's exterior cusp and plasma mantle, where the ionospheric origin escaping ions with finite temperatures are loaded into the decelerated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 63 publications
0
17
0
Order By: Relevance
“…The first CME, which arrived late 6 September, had northward IMF with 600‐km/s velocity, whereas the second that arrived late 7 September had southward IMF with 800‐km/s velocity. These features are most likely the causes of higher‐scaled O + outflow because both velocity and IMF are expected to influence O + outflow (Lennartsson et al, ; Yamauchi & Slapak, ). Lennartsson et al () showed that negative IMF B z has a higher influence on the total O + outflow by approximately a factor 3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first CME, which arrived late 6 September, had northward IMF with 600‐km/s velocity, whereas the second that arrived late 7 September had southward IMF with 800‐km/s velocity. These features are most likely the causes of higher‐scaled O + outflow because both velocity and IMF are expected to influence O + outflow (Lennartsson et al, ; Yamauchi & Slapak, ). Lennartsson et al () showed that negative IMF B z has a higher influence on the total O + outflow by approximately a factor 3.…”
Section: Discussionmentioning
confidence: 99%
“…However, Nilsson et al () showed that O + is less accelerated during BBFs than the dominating protons. Finally, high O + escape into the inflow solar wind plasma leads to a high mass loading rate and high extraction rate of the solar wind kinetic energy to the ionosphere in a limited and small region at high latitudes (Yamauchi & Slapak, ). Therefore, we expect ground‐induced currents at much higher latitudes than normal.…”
Section: Discussionmentioning
confidence: 99%
“…These low-latitude instruments (around 19 ∘ N geographic latitude, and 29 ∘ N geomagnetic latitude) record data in a region where the space weather effects have not been studied sufficiently due to the lack of the historical records (Denardini et al, 2016). Recently, De la Luz et al (2018) registered, for the first time, global space weather effects over Mexico (ionospheric and geomagnetic disturbances, variations in cosmic rays fluxes, and radio communication's interferences) for two particular events: 22 June 2015 and 29 September 2015. It is noteworthy that during this interval of a few days of high solar activity in September 2017, the Mexican region was affected also by other natural hazards.…”
Section: Introductionmentioning
confidence: 99%
“…Ion escape during space weather events has additional importance because Schillings et al () found that the escaping O + flux for Kp > 7 can be higher than the predicted values from the exponential Kp dependence for Kp ≤ 7. The results suggest that (1) past ion loss from the ionosphere could have been larger than the above estimate (Yamauchi & Slapak, ) and (2) the energy extraction and relevant space weather hazards in the polar region can be even larger than predicted by any existing model using our knowledge for ordinary conditions of Kp < 7. Indeed, there is no guarantee that the response of the high‐latitude ionosphere to extreme solar and interplanetary space weather conditions stays within the expected range from ordinary active conditions through UV ionization, particle precipitations, and electromagnetic energy input represented by, for example, Akasofu's coupling function (Akasofu, ; Newell et al, , ).…”
Section: Introductionmentioning
confidence: 53%
“…Such a nonlinear dependence on Kp also exponentially enhances energy extraction from the solar wind to the cusp current system through the mass‐loading effect of the escaping ions, i.e., inelastic mixing of escaping ions and incoming solar wind ions (Yamauchi & Slapak, , ), enhancing the risk of space weather hazards in that local region. Thus, the ionosphere plays two important roles in ion escape, one energizing the ionospheric ions through various energization mechanisms (e.g., André & Yau, ) such as Joule heating (Brekke & Rino, ) and the other extracting energy from the solar wind through the mass‐loading effect of the escaping ions.…”
Section: Introductionmentioning
confidence: 99%